A Magnet-Controlled and Renewable Amperometric Immunosensor for Carcinoembryonic Antigen Based on Magnetic Fe3O4(core)/Au(shell) Nanoparticles Modified Screen-Printed Carbon Electrode - Gan, Ning; Meng, Linghua; Li, Tianhua; Cao, Yuting; Zheng, Lei (Asian Journal of Chemistry, 2011)
A novel amperometric immunosensor for carcinoembryonic antigen (CEA) was fabricated. Firstly, multi-walled carbon nanotubes with carboxyl groups (MCNTs)-thionine (Thi)-Nafion composite was prepared and dropped on the surface of a screen-printed working electrode (SPCE) to prepare the basic electrode (SPCE|MCNTs-Thi-Nafion). Secondly, horseradish peroxidase (HRP) labeled carcinoembryonic antigen antibody (HRP anti CEA) and bovine serum albumin (BSA) were assembled on Fe3O4(core)/Au(shell) nanoparticles (GMPs) to form the nanoprobes, which were introduced on the surface of the basic electrode by permanent magnet. Through one-step immunoassay format, the immunosensor was incubated with carcinoembryonic antigen. The formed antigen-antibody complex inhibited partly the active center of horseradish peroxidase labeled on anti carcinoembryonic antigen, which led to a linear decrease in the catalytic efficiency of horseradish peroxidase to the oxidation of immobilized thionine by H2O2. Under optimized conditions, the decreased current was proportional to the carcinoembryonic antigen concentration from 0.1-5.0 and 5.0-80 ng mL-1 with a detection limit of 0.03 ng mL-1 at signal/noise ratio of 3.